Cancer, platelet distribution width, and total protein levels as predictors of rebleeding in upper gastrointestinal bleeding - Ali Cankut Tatlıparmak; Özlem Dikme; Özgür Dikme; Hakan Topaçoğlu (PeerJ, 2022)
Background Rebleeding is associated with poor outcomes in upper gastrointestinal bleeding (UGIB). Identifying predictors of rebleeding can assist in risk assessment. The aim of the study is to investigate the factors affecting rebleeding in patients with UGIB admitted to the emergency department. Methods This retrospective, observational, cross-sectional study was conducted on patients with UGIB presented to the emergency department. Patients who did not arrest in the first 24 h, who were not diagnosed with GI malignancy, and who were clinically diagnosed with UGIB were included in the study. Patient demographic characteristics, hemodynamic parameters, patient parameters, and bleeding that may affect rebleeding were evaluated. The primary endpoint was rebleeding within 7 days. Results The study included 371 patients. A total of 55 patients (14.8%) had rebleeding within 7 days, and 62 patients (16.7%) presented without bleeding manifestations. Rebleeding rates were higher in those who presented with bloody or coffee-ground vomitus, had a diagnosis of cancer, had blood in their nasogastric tube, and had peptic ulcers due to endoscopy. Mean cell hemoglobin concentration, lymphocyte, albumin, and total protein values of patients with rebleeding were low; red blood cell distribution width, neutrophil count, platelet distribution width (PDW), and neutrophil lymphocyte ratio were high. In-hospital mortality and 30-day mortality values of patients with rebleeding were significantly increased. In the multivariate analysis, cancer, PDW, and total protein levels were statistically significant. Conclusion The presence of cancer, low total protein level, and high PDW are effective parameters in predicting 7-day rebleeding in patients with UGIB admitted to the emergency department.